KERALA MODEL OF DEVELOPMENT: ISSUE OF SUSTAINABILITY. - Anand Jayakrishnan K. (Int. J. Adv. Res., 2016)
Kerala was able to achieve high living standards matched by high developed nations despite performing relatively lower on various economic indicators when compared to them. This development experience had been christened as „Kerala model of development‟ in academic circles. A series of academic discussions began around late 1980s highlighting the unsustainability of such a model. With the recent implementation of stringent NITAQAT laws by middle east nations and booming return migration, Kerala was forced to reconsider the development pattern so far followed and issue of sustainability as never before. The present article examines the question of sustainability of Kerala development model in detail.